Edukasi dan Pemeriksaan Dini Gaya Hidup Sehat Melalui Pengendalian Gula Darah - Yulita Maulani; Emma Ismawatie; Edy Purwanto; Laela Siti Musrikatun (JURNAL PENGABDIAN KESEHATAN, 2025)
Diabetes Mellitus (DM) is a chronic metabolic condition characterized by elevated blood sugar levels, often attributed to unhealthy lifestyles and insufficient early detection. This activity aimed to enhance public knowledge and facilitate early blood sugar screening at Solo Grand Mall, Surakarta City, as a proactive promotional and preventive measure against the increasing prevalence of DM. The methodology employed in this community service initiative included educational presentations on healthy lifestyles and blood sugar control, alongside free blood sugar tests for interested mall visitors, with support from PT Edsa Setia Abadi. The outreach and screening activities garnered significant enthusiasm from participants, evidenced by the large number of active attendees. This initiative successfully imparted crucial knowledge regarding the importance of healthy living and early DM detection to the community of Solo and its surrounding areas. It is hoped that following this event, the public will apply the acquired knowledge in their daily lives. Furthermore, the sustained continuation of educational programs and regular screenings, supported by various stakeholders, is essential to effectively prevent and control DM.